Çimento hamurlarının mekanik özelliklerine CO2 Kürünün etkisi - Yüksel, Merve; Özcan, Ahmet; Toprak, Mehmet Uğur (Afyon Kocatepe Üniversitesi)
Erken yaşta CO2 kürü, çimento hidratasyon ürünlerinin oluşumunu etkileyerek çimento bağlayıcılı malzemelerin mekanik özeliklerini değiştirebilmektedir. Farklı su/çimento (s/ç) oranlarında (%28 ve %32) çimento hamurları hazırlandıktan sonra 4 farklı şekilde CO2 kürü uygulanmıştır. Çimento hamurlarının karıştırma işlemi bittikten 15 dk sonra numunelere 15, 30 ve 60 dk CO2 kürü (1, 3, 5, 8 ve 10 bar) uygulanmıştır. Aynı zamanda numunelerin bir kısmına da priz başladıktan sonra (117 dk) 30 dk CO2 kürü (1, 3, 5, 8, 10 ve 50 bar) uygulanmıştır. Çimento hamurlarının 7 günlük basınç dayanımları incelenmiştir. En yüksek basınç dayanımı (112.73 MPa) 15 dk ön bekleme yapılmış ve 60 dk süresince 3 bar CO2 kürü uygulanmış KK %28 kodlu numunede elde edilmiştir. Kontrol numunelerinde s/ç oranı arttığında basınç dayanımındaki azalma %27 iken, 15 dk ön beklemeden sonra 60 dk CO2 kürü uygulanan numunelerdeki bu azalma oranı %53’dür. Dayanım artışı açısından genel olarak çimento hamuruna uygulanan en uygun kür işlemi 15 dk ön bekleme sonunda 60 dk 3 bar CO2 kürüdür.

CO2 curing at an early age can change the mechanical properties of cement-binding materials by affecting the formation of cement hydration products. After the cement pastes were prepared at different water/cement (w/c) ratios (28% and 32%), CO2 curing was applied in 4 different ways. 15 minutes after the mixing process of the cement pastes was completed, CO2 curing (1, 3, 5, 8 and 10 bar) was applied to the samples for 15, 30 and 60 minutes. At the same time, 30 minutes of CO2 curing (1, 3, 5, 8, 10 and 50 bar) was applied to some of the samples after setting (117 minutes). The 7-day compressive strengths of cement pastes were investigated. The highest compressive strength (112.73 MPa) was obtained in the KK 28% coded sample, which was kept for 15 minutes and then cured with 3 bar CO2 for 60 minutes. While the decrease in compressive strength was 27% when the w/c ratio in the control samples increased, this decrease rate was 53% in the samples cured with CO2 for 60 minutes after 15 minutes of pre-waiting. In terms of strength increase, the most suitable curing process applied to cement paste, in general, was 3 bar CO2 curing for 60 minutes after 15 minutes of pre-waiting.
Effect of CO2 Curing on mechanical properties of cement pastes
Keywords: Basınç dayanımı; CO2 Kür; Çimento Hamuru; Su/çimento Oranı; Compressive Strength; CO2 Curing; Cement Paste; Water/Cement Ratio